Papierherstellung im deutschen Südwesten Ein neues Gewerbe im späten Mittelalter - Schultz, Sandra (Materiale Textkulturen, 2018)
The series Material Text Culturess the publication organ of the Collaborative Research Center 933 of the same name at Heidelberg University, funded by the German Research Foundation (DFG). The series publishes collections and monographs dedicated to the Collaborative Research Center's main focus of research - that is, the materiality and presence of writing in non-typographic societies.